(untitled) (Research, Society and Development, 2023)
Nosocomial infections are complications of extreme relevance of hospital origin that have an impact on the patient’s health, which also compromises on the care safety of the hospital environment. Thus, the present study aims to identify the bacteria Staphylococcus aureus and Pseudomonas aeruginosa in samples collected from fômites, cellular and stsoscopic from health professionals in a private hospital in Annapolis. This is a qualitative-quantitative, field, exploratory research with a cross-sectional design. This research used 50 cell samples and stethoscopes from health professionals. Fifty samples were evaluated: 29 cell phones and 21 stethoscopes. Contamination of 93.10% of cell phones and 95.23% of stethoscopes were obtained. As for growth in Manitol Agar medium, indicative of Staphylococcus spp. bacteria, bacterial colonies growth was found in 89.65% of cell phones and 95.23% of stethoscopes. In macconkey agar medium, ideal for gram-negative bacilli, bacterial colony growth was found in 31% of cell phones and 23.8% of stethoscopes. Regarding the frequency of hygiene, the prevalence of action daily is perceived both in cell phones and in stethoscopes, with 34.4% and 76%, respectively. Alcohol was the most used method for the hygiene of cell phones and stethoscopes, with 65.5% and 85%, respectively. Alcohol was the most used method for the hygiene of cell phones and stethoscopes, with 65.5% and 85%, respectively. Regarding the importance attributed to the hygiene of mobile phones, 31% of responses were obtained and considered very important. In stethoscopes, there is a predominance in high importance with 80.9%. The present study was of paramount importance, because there was a considered rate of contamination in cell phones and stethoscopes of health professionals.